Transnational spaces: the migrant experience across the Americas - Álvarez, Soledad (Ruperto Carola, 2022)
As a result of new global and regional migratory patterns, migration has been on the rise across the Americas. In the past decade, two extended migratory corridors have emerged, connecting the Andean Region with Central America, Mexico and the US towards the north, and with the countries of the Southern Cone towards the south. Products of power relations around migrant mobility and control, these corridors have given rise to new geographies and new forms of mobility. How the tension between undocumented migrant mobility and reinforced border control regimes across the Americas gives rise to spatial and temporal transformations is the subject of ethnographic research carried out by scientists at the Heidelberg Center for Ibero-American Studies.